2021
DOI: 10.21203/rs.3.rs-754084/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Prenatal Central Nervous System Anomalies: Obstetric Management, Fetal Outcomes and Chromosome Abnormalities

Abstract: Objective: To study the prognostic outcomes of fetuses with prenatally diagnosed central nervous system (CNS) anomalies and describe the obstetric management for those fetuses.Methods: In this retrospective study, fetuses who were detected to have central nervous system by prenatal ultrasound from January 2010 to December 2019 were recruited. Data regarding prenatal diagnosis and obstetric outcome were retrieved from maternal and paediatric records. Prognosis of children who survived till delivery was classifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…In pregnant women with prenatal fetal central nervous system malformation, termination rates have been reported as 48-60% and live birth rates as 35-47% (29). Also, in the study performed by Tan Ag et al (30), the termination rate was found to be 48.2% in pregnant women with fetal central nervous system anomaly; It was stated that 92.7% of these were done by medical induction, and only 7.3% of them were terminated by surgical method. In our study, the termination rate was lower than the literature, and the live birth rate was higher than the literature.…”
Section: Discussionmentioning
confidence: 96%
“…In pregnant women with prenatal fetal central nervous system malformation, termination rates have been reported as 48-60% and live birth rates as 35-47% (29). Also, in the study performed by Tan Ag et al (30), the termination rate was found to be 48.2% in pregnant women with fetal central nervous system anomaly; It was stated that 92.7% of these were done by medical induction, and only 7.3% of them were terminated by surgical method. In our study, the termination rate was lower than the literature, and the live birth rate was higher than the literature.…”
Section: Discussionmentioning
confidence: 96%